Inter-epidemic Rift Valley fever virus seroconversions in an irrigation scheme in Bura, south-east Kenya - Mbotha, D.; Bett, Bernard K.; Kairu-Wanyoike, S.W.; Grace, Delia; Kihara, Absolomon; Wainaina, M.; Hoppenheit, A.; Clausen, Peter-Henning; Lindahl, Johanna F. (Hindawi Limited, 2018)
Rift Valley fever (RVF) is an acute mosquito-borne viral zoonosis whose outbreaks are often associated with prolonged rainfall and flooding, during which large numbers of vectors emerge. Recent studies into the inter-epidemic maintenance of RVF virus (RVFV) suggest that both vertical transmission in vectors and direct transmission between hosts act in combination with predisposing factors for persistence of the virus. A comparative longitudinal survey was carried out in Tana River County, Kenya, in irrigated, riverine and pastoral ecosystems from September 2014–June 2015. The objectives were to investigate the possibility of low-level RVFV transmission in these ecosystems during an inter-epidemic period (IEP), examine variations in RVFV seroprevalence in sheep and goats and determine the risk factors for transmission. Three hundred and sixteen small ruminants were selected and tested for immunoglobulin G antibodies against RVFV nucleoprotein using a competitive ELISA during six visits. Data on potential risk factors were also captured. Inter-epidemic RVFV transmission was evidenced by 15 seroconversions within the irrigated and riverine villages. The number of seroconversions was not significantly different (OR = 0.66, CI = 0.19–2.17, p = .59) between irrigated and riverine areas. No seroconversions were detected in the pastoral ecosystem. This study highlights the increased risk of inter-epidemic RVFV transmission posed by irrigation, through provision of necessary environmental conditions that enable vectors access to more breeding grounds, resting places and shade, which favour their breeding and survival.